Molecular identification of Sarcocystis lutrae in the European otter (Lutra lutra) and the European badger (Meles meles) from the Czech Republic - Máca, Ondřej (Parasitology research, 2018)
Muscular sarcosporidial infections by Sarcocystis lutrae (Apicomplexa: Sarcocystidae) from the otter (Lutra lutra) and badger (Meles meles) (Carnivora: Mustelidae) were found in the Czech Republic. As part of a diversity evaluation of Sarcocystis in wild carnivores during 2016-2017, samples of diaphragm, tongue and hind-limb muscles were collected from nine districts, examined by compression and characterized molecularly. Cyst walls were thin, with no visible protrusions, and histological sections of infected muscle tissue showed no host responses. Fourteen of 17 badgers (82% prevalence) and one otter (100% prevalence) were positive for sarcocysts. Sequence analyses at four loci (18S rRNA, 28S rRNA, ITS1 and cox1) confirmed the identity as S. lutrae. This is also the first report of a co-infection with muscular sarcocystosis and Trichinella in badger. The finding of Trichinella is important from the zoonotic point of view, since badgers are used for meat consumption. Similar and future monitoring of both parasitic taxa are needed.
Keywords: RNA, Ribosomal; Polymerase Chain Reaction; molekulární typizace; sarkocystóza; koinfekce; RNA ribozomální; zvířata; vydry; Czech Republic; Trichinellosis; Sarcocystosis; Česká republika; Otters; trichinelóza; svaly; Molecular Typing; polymerázová řetězová reakce; Sarcocystis; Muscles; Trichinella; Animals; Coinfection; Carnivora